Nitrogen and phosphorous losses in semi-intensive mono and polyculture systems: very significant difference between fed and unfed ponds - Rahman, Mohammad Mustafizur; Verdegen, M.C.J.; Wahab, M.A.; Verreth, J.A.J. (2005)
Nitrogen and phosphorous are two important key elements in aquaculture production system. So, understanding of nitrogen and phosphorous losses as well as incorporations into in different production system are also very important to reduce eutrophication, and to achieve higher fish production. However, due to lack of real recommendation on how nitrogen and phosphorous are lost and incorporated into in semi-intensive mono and polyculture systems, an experiment was conducted to know the quantity of nitrogen and phosphorous losses and incorporations into in semi-intensive mono and polyculture systems. The experiment was conducted in earthen ponds having six treatments with three replications. All ponds were fertilized with fertilizers: 1,250.0 kg ha-1 decomposed cow manure, 31 kg ha-1 urea and 157 kg ha-1 triple super phosphate before beginning of the experiment and thereafter fortnightly intervals. Two monoculture treatments (one receiving supplementary feed and another receiving no feed) were stocked with 15,000 rohu (Labeo rohita) ha-1. Among four polyculture treatments, two treatments (one receiving supplementary feed and another no feed) were stocked with 15,000 rohu plus 5,000 common carp (Cyprinus carpio) ha-1 and rest two (one receiving supplementary feed and another no feed) were stocked with 15,000 rohu plus 10,000 common carp ha-1. After four and half months long experiment, it was found, average nitrogen and phosphorous losses were higher in monoculture system than in polyculture system, conversely; average percent incorporation of nitrogen and phosphorous into were higher in polyculture system than in monoculture system. Similar relations were observed when compared between fed and unfed systems. Nitrogen and phosphorous losses were higher in treatments with feed than the treatments with no feed, conversely; nitrogen and phosphorous incorporation into were in treatments with feed than the treatments with no feed. These results may also be affected on types of cultured physico-chemical properties of pond as well quality and quantity of supplementary feed.